Perancangan Purwarupa Sistem Informasi Online Pendistribusian dan Persediaan Logistik Saat Tanggap Darurat Bencana di BPBD Pidie Jaya - Zulfadli Zulfadli; Nizamuddin Nizamuddin; Nasaruddin Nasaruddin (Fakultas Teknik, 2019)
Logistics supply when emergency of disaster comes up that have some problems to be considered much as setting up of emergency operations center irregularly, less coordination between sectors, the data of victims is not properly recorded, and the logistics supply not appropriate with the need of victims. These problems occured because there are no information connected between sectors related to victim data, and the aid that has been fulfilled is very urgent logistics at the disaster site. Information system for distribution and logistics supplies during disaster response is needed to realize effective and efficient distribution. This information system design includes planning, system analysis, collecting data, system design, system testing and implementation. This research was conducted at BPPD office in Pidie Jaya Regency. This information distribution and logistics inventory system that is designed will simplify and accelerate the process of recording in distribution and logistics supply. The results of this system can be introduced to society, so that when disaster occurs the community will receive information quickly and accurately related to distribution and logistics supply